PENDAMPINGAN REORGANISASI KEPENGURUSAN KOMITE SD ISLAM ASSAKINAH BATAM - Prasetyo, Ary; Sari, Asih Purwana; Suratman, Suratman; Purba, Daris (EJOIN : Jurnal Pengabdian Masyarakat, 2023)
The School Committee has a very important role in helping to improve the quality of education in schools. The reorganization of the SDI Assakinah Batam School Committee is necessary because the management of the SDI Assakinah Committee for the 2021-2023 period has ended. By carrying out community service through assistance in reorganizing the management of the SDI Assakinah Committee, it is hoped that participants will be able to understand the stages or process of changing committee management. From the results of the mentoring, 90% of participants understood the process of changing management or reorganizing the School Committee.   ABSTRAK Komite Sekolah mempunyai peran yang sangat penting dalam membantu meningkatkan mutu pendidikan di sekolah. Reorganisasi Komite Sekolah SDI Assakinah Batam diperlukan karena sudah berakhirnya kepengurusan Komite SDI Assakianah periode tahun 2021-2023. Dengan dilakukan pengabdian masyarakat melalui pendampingan reoranisasi kepengurusan Komite SDI Assakinah, diharapkan perserta dapat memahami tahapan atau proses pergantian kepengurusan komite. Dari hasil pendampingan sebanyak 90% peserta memahami proses pergantian kepengurusan atau reorganisasi Komite Sekolah.